An analysis of the library usage patterns of comparative literature students at the College of Arts and Letters, University of the Philippines Diliman - Tolentino, Chiara Rica T. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study sought to analyze and assess the library usage patterns of comparative literature students of the University of the Philippines College of Arts & Letters and their relationship to specific personal and environment factors. The personal factors included age, gender, year level, student status and the distance of residence from campus. Environment factors considered are the faculty influence and the library services, facilities, and resources. Particularly, this study sought to determine how the comparative literature students evaluate the library's services, facilities, and resources specifically if: (1) the users are aware of the UP College of Arts and Letters Library collection; (2) the condition of the library's services, facilities, and resources, as evaluated by the comparative literature students, have a significant relationship with their library usage pattern; and (3) determine the problems encountered by the comparative literature students when using the UP College of Arts and Letters Library. Finally, the study sought to offer recommendations and suggestions for the improvement of the UP College of Arts and Letters Library.